Efficient ways of communicating time-of-use electricity tariffs in Ireland: Plain and simple - Martina Barjaková; Cameron Belton; Karl Purcell; Pete Lunn (The Economic and Social Research Institute (ESRI), 2021)
With the ongoing rollout of smart meters in Ireland, time-of-use (ToU) tariffs are currently being introduced as a new way to pay for electricity. Such tariffs can bring important benefits to both consumers and society, in terms of reduced electricity bills and CO2 emissions, respectively. At the same time, some consumers may find it more difficult to benefit from ToU tariffs than others. Communication around ToU tariffs thus needs to explain both benefits and challenges successfully; it needs to encourage ToU uptake, while enhancing comprehension. This paper presents results from a pre-registered experiment that pre-tested behaviourally-informed communications on ToU tariffs. A large, representative sample of consumers (n=1,300) viewed an experimentally manipulated primer on ToU tariffs before completing a series of tasks to measure their views, objective comprehension, and tariff choices. In general, consumers were positive towards ToU tariffs, viewing monetary savings as a primary benefit. Environmental framing of information enhanced positivity among younger participants. Comprehension and choice quality were rather modest, but improved when tariff examples were presented in a plain table, compared to 24h clock formats. This finding is important as the latter are commonly used in the market. The study demonstrates the benefit of experimentally pre-testing policy interventions.
Keywords: C99; D12; D83; Q41; 330; time-of-use tariffs; consumer choice; policy pre-testing; behavioural economics